Problems of income taxes of professional athletes in team sports - Lenka Bartková (Palacký University Olomouc, 2010)
The article is focused on problems of income taxes of professional athletes in team sports. A part of those problems is a legal form of professional athletes in so-called team sports, which is still quaere in scientific discussion. In the article, there are took into account also opinions of scientists and managers on initially prepared amendment of act about income taxes, which supposed to be concerned in status of professional athlete in team sports. The second part of the article is focused on problems of income taxation those athletes.